0172 Effects of Daytime Sleepiness on Working Memory Performance in Veterans With and Without PTSD. (12th April 2019) - Khan, Hassen; Wallace, Meredith J; Laxminarayan, Srinivas; Ramakrishnan, Sridhar; Reifman, Jaques; Germain, Anne
Abstract: Introduction: Working memory (WM) is a cognitive system responsible for temporarily storing and manipulating newly-acquired information. WM may be impacted by daytime sleepiness resulting from chronic sleep disturbances that characterize posttraumatic stress disorder (PTSD). We evaluated whether WM performance varied as a function of daytime sleepiness in Veterans with and without PTSD on the 2-Back task. We hypothesized that daytime sleepiness, measured by the multiple sleep latency test (MSLT) would predict accuracy and mean reaction time (RT), and that PTSD status would interact with sleep latency to influence WM performance. Methods: Thirty-seven Veterans with PTSD and 48 Veterans without PTSD completed a 48-hour laboratory stay. Daytime sleepiness was measured by average sleep latency on the MSLTs on day 2. Following each MSLT, a n-Back WM task was administered. The 2-Back WM parameters of interest included accuracy and mean RT. Independent t-tests and non-parametric Mann-Whitney U tests were used to compare daytime sleepiness effects on WM performance between groups. Sleep latency was split into high (SL>5) and low (SL≤ 5) groups. Linear regressions were used to test the interaction between diagnostic group, sleep latency on WM. Results: Daytime sleepiness did not differ between Veterans with and without PTSD (t(83)=-.10, p =.92). However, the PTSD group showed reduced accuracy (U=622, p =.02) and increased mean RT (U=625, p =.02) compared to the non-PTSD group on the 2-Back WM task. Overall, sleep latency did not independently predict WM performance for accuracy (β=.06, p=.60) or mean RT (β=-.08, p=.45). There was no significant interaction between diagnostic group and sleep latency group for either accuracy or RT. Conclusion: Working memory performance is a key cognitive process for problem-solving and reasoning ability. The results suggest that even if Veterans with PTSD do not exhibit heighted daytime sleepiness, they show detectable WM impairments. The extent to which overnight sleep and daytime vigilance may interfere with higher executive functions, such as WM, in PTSD remain to be evaluated. Support (If Any): USAMRMC MOMRP PT 130572(PI: Reifman).The opinions and assertions contained herein are the private views of the authors.